Luteolin attenuates glucocorticoid‐induced osteoporosis by regulating ERK/Lrp‐5/GSK‐3β signaling pathway in vivo and in vitro. Issue 4 (7th September 2018) - Jing, Zheng; Wang, Changyuan; Yang, Qining; Wei, Xuelian; Jin, Yue; Meng, Qiang; Liu, Qi; Liu, Zhihao; Ma, Xiaodong; Liu, Kexin; Sun, Huijun; Liu, Mozhen
Abstract: Glucocorticoid‐induced osteoporosis (GIO) is a secondary osteoporosis with extensive use of glucocorticoids (GCs). GCs can increase bone fragility and fracture via inhibiting osteoblastic proliferation and differentiation. Luteolin (LUT), a kind of plant flavonoid, has been reported to exhibit the antioxidant activity, but the effects of LUT on GIO still remain unclear. This study aimed to investigate the effects of LUT on GIO both in vivo and in vitro and elaborate the potential molecular mechanisms. LUT increased the superoxide dismutase activity, glutathione level and decreased reactive oxygen species (ROS) level and lactate dehydrogenase release in GIO. Meanwhile, LUT decreased caspase‐3, caspase‐9, and Bax protein expressions and increased Bcl‐2 protein expression in GIO. LUT increased the ratio of osteoprotegerin (OPG)/receptor activator of nuclear factor‐κB Ligand (RANKL) messenger RNA (mRNA) expression and mRNA expression levels of osteogenic markers, including runt‐related transcription factor 2, osterix, collagen type I, and osteocalcin. LUT also enhanced the extracellular signal‐regulated kinases (ERK) phosphorylation, glycogen synthase kinase 3β (GSK‐3β) phosphorylation, mRNA expression levels of lipoprotein‐receptor‐related protein 5 (Lrp‐5) and β‐catenin. Further study revealed that Lrp‐5 small interfering RNA (siRNA )and ERK‐siRNA reduced the effects of LUT on GSK‐3β phosphorylation, alkaline phosphatase (ALP) activity and the ratio of OPG/RANKL mRNA expression. Moreover, ERK‐siRNA decreased Lrp‐5 mRNA expression in vitro. These results indicated that LUT promoted proliferation by attenuating oxidative stress and promoted osteoblastic differentiation by regulating the ERK/Lrp‐5/GSK‐3β pathway in GIO. This study may bring to light the possible mechanisms involved in the action of LUT in GIO treatment, and benefit for further research on GIO. Abstract : Luteolin (LUT) could inhibit osteoblastic apoptosis via inhibiting oxidative stress in glucocorticoid‐induced osteoporosis (GIO). Moreover, LUT could promote osteoblastic differentiation via the extracellular signal‐regulated kinases (ERK)/lipoprotein‐receptor‐related protein 5 (Lrp‐5)/glycogen synthase kinase 3β (GSK‐3β) signaling pathway in GIO.